2020
DOI: 10.1073/pnas.1910597117
|View full text |Cite
|
Sign up to set email alerts
|

Short-wavelength optoacoustic spectroscopy based on water muting

Abstract: Infrared (IR) optoacoustic spectroscopy can separate a multitude of molecules based on their absorption spectra. However, the technique is limited when measuring target molecules in aqueous solution by strong water absorption at IR wavelengths, which reduces detection sensitivity. Based on the dependence of optoacoustic signal on the temperature of the probed medium, we introduce cooled IR optoacoustic spectroscopy (CIROAS) to mute water contributions in optoacoustic spectroscopy. We showcase that spectral mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Figure 5 shows the extracted peak-to-peak values of THz-OA signals of NaCl solutions and pure water. Linear fitting was used to figure out the muting temperature of each solution ( Prakash et al., 2020 ; Xu et al., 2021 ). The muting temperatures of aqueous solutions with NaCl concentrations of 0.01, 0.02, 0.03, and 0.04 mol/L were calculated to be 3.73, 3.40, 3.23, and 3.01°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the extracted peak-to-peak values of THz-OA signals of NaCl solutions and pure water. Linear fitting was used to figure out the muting temperature of each solution ( Prakash et al., 2020 ; Xu et al., 2021 ). The muting temperatures of aqueous solutions with NaCl concentrations of 0.01, 0.02, 0.03, and 0.04 mol/L were calculated to be 3.73, 3.40, 3.23, and 3.01°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At 4 o C, due to β water = 0 for water, the local pressure of aqueous solution based on water muting method and Despretz law can be further written as ( Prakash et al., 2020 ) where c is the solute concentration, and β 2 , K is a constant in thermal coefficient of volume expansion and Despretz law respectively, which are determined by aqueous solution. In different low concentration aqueous solution, the change of β 2 , K , V S , C P , η th and μ a can be ignored ( Wang and Wu, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, there is a larger deviation between the ink and melanin-producing E. coli compared to the controls when using MSOT than when using a spectrometer, particularly visible in the pronounced drop around 900 nm. This deviation might be due to several factors like non-linear variations in fluence distribution across different wavelengths, fluctuations in laser energy at different wavelengths, the spatial impulse response of the transducer, temperature-dependent thermal conversion factors (Grüneisen parameter) and optical scattering 22 25 . In summary, these results indicate that tyrosinase-expressing E. coli can produce melanin that can be detected by MSOT in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the researchers also explored the effect of temperature on the detection in glucose solution. Through experiments, Prakash et al found that the photoacoustic signal of pure water in the wavelength range from 900 to 1840 nm became mute at 4 ℃, based on which they proposed cooled IR photoacoustic spectroscopy (CIROAS) to mute the contributions of water to the PAS of glucose solution [ 50 ]. Compared with traditional PAS, the technique effectively improves the detection sensitivity in glucose solution.…”
Section: Non-invasive Monitoring Methods Based On Photoacoustic Spect...mentioning
confidence: 99%